The effect of preparation methods condition on the activity of palladium and platinum catalysts towards hydrogenation of palm olein - Salimah, Shafii (2012)
The hydrogenation of vegetable oils is an important practice in the modification of fats and oils especially to increase the stability of the oil. Highly unsaturated oil is susceptible to autoxidation, thermal decomposition and other reactions that affect the quality and flavor. Consequently, it is desired to partially hydrogenate the oil to improve shelf life. Another reason to hydrogenate vegetable oils is to improve its utility. The effect of ultrasonic irradiation (US) and microwave (MW) on the preparation of mono- and bimetallic Pd and Pt were compared with the conventional heating (CH) method. Besides that, their activities for the hydrogenation reaction of palm olein were also reported. The Pd, Pt and PdPt nanoparticles stabilized with polyvinylpyrrolidone (PVP) were prepared with molar ratio of PVP to metal of 40:1. Small size particles that are highly dispersed were obtained after 2, 10 and 40 min under MW for Pd, PdPt and Pt colloidal nanoparticles respectively. The average particles size for Pd, Pt and PdPt was 1.24, 1.03 and 1.05 nm respectively. Meanwhile US also enhanced the reduction process, where reduction process completed after 5, 30, and 60 min for Pd, Pt and PdPt nanoparticles. However, large particle sizes were obtained under ultrasonic irradiation.The Pdnanoparticles have bimodal distribution with average sizes of 1.37 and 2.68nm.The Pt and PdPt nanoparticles have only one distribution with average particles size of 1.42 and 1.28nm respectively. Whereas, CH method with takes 3 hours has produced Pd, Pt and PdPt with particles sizes of 0.99, 1.20 and 1.23nm. The XRD analysis has strengthen the TEM result obtained, where broad peak obtained described small particles produced. From the XRD data, particles sizes were also re-calculated by using the Scherer equation and compared with the TEM result. It has shown that, the particles sizes calculated using the Scherer equation are slightly higher than that of the TEM result. Based from the XPS analysis, surface compositions of Pd and Pt show that PdPt(CH) and PdPt(MW) catalyst were in core-shell structure, meanwhile PdPt(US) was in alloy formation.The hydrogenation reaction of palm olein was conducted under ambient temperature and pressure with the molar ratio of palm olein to catalyst of 25000:1. The result shows that Pd(CH), Pt(MW), and PdPt(MW) catalysts achieved higher linoleate conversion. The conversion of linoleate, elaidate selectivity and iodine values (IVs) are increased in order of Pt<PdPt<Pd. Elaidate selectivity for Pd, Pt, and for PdPt catalysts (includedprepared under CH, MW, and US) were at range 52-56%, 3.5-8%, 4.4-13.4% respectively. The IVs for Pd nanoparticles are slightly decreased from 57 to range of 41-43 after 180 min reaction time. On the other hand, IVs for Pt and PdPt shows highly decreased from 57to minimum values of to 38 and 39 respectively. The hydrogenation reaction under ultrasonic irradiation has enhanced the catalytic reactivity. Statistical analyses had proved that different types of catalyst, method of catalyst prepared and reaction conditions give a significant effect on the composition of linoleate, oleate, elaidate and stearate.